(untitled) (Bangladesh Journal of Medical Microbiology, 2012)
Critically ill patients acquire an infection during their stay in an intensive care unit (ICU) and the frequency of these infections varies considerably in different populations and clinical settings. The purpose of this study was to know the antimicrobial sensitivity pattern of Acinetobacter isolates from tracheal aspirate, blood from central venous catheter, peripheral blood, urine and endotracheal tube of patients admitted in ICU at BSMMU(Bangabandhu Sheikh Mujib Medical University) hospital, Dhaka, Bangladesh over a one year period from January 2010 to December 2010. A total 95 ICU samples were studied of which 32(33.7%) were Acinetobacter species. Acinetobacter species isolated from endotracheal tube (100%), tracheal aspirate (54.3%), blood from central venous catheter (36.4%), peripheral blood (13.6%), and urine (12.5%). Acinetobacter isolates were 100% resistant to amoxicillin, ceftriaxone cefuroxime and gentamicin. Higher level of resistance was recorded for amikacin (68.4%) and imipenem (66.7%). Lower resistance only showed in colistin (10.5%). The findings of this study will help our clinician to apply antibiotics for treatment of the patients admitted in ICU. Producing a local antibiogram database will improve the knowledge of antimicrobial resistance patterns in Bangladesh and will also help to improve treatment strategies. DOI: http://dx.doi.org/10.3329/bjmm.v6i1.19352 Bangladesh J Med Microbiol 2012; 06(01): 3-6